Sarcolobus globosus subsp. peregrinus, a newly recorded subspecies of Sarcolobus (Apocynaceae) from Zhanjiang, China - Deng, Shuangwen; Lin, Guangxuan; Li, Zixiang; Li, Yali; Xu, Lei; Yu, Qianxia; Xing, Fuwu; Wang, Faguo (Phytotaxa, 2023)
A newly recorded subspecies, Sarcolobus globosus subsp. peregrinus (Blanco) Rintz, was reported. This subspecies was previously known to be distributed in Southeast Asia islands, which was recently found in Zhanjiang, Guangdong, China. Detailed morphological description, field photos and geographical distribution are provided in this study. Additionally, the whole chloroplast genome was sequenced by the Illumina sequencing technology. The annotated results revealed that the chloroplast genome has a conserved quadripartite structure, with a pair of inverted repeat regions (IRs) separating the large single copy (LSC) region from the small single-copy (SSC) region, resulting in a total length of 161,561 base pairs (bp). The phylogenetic analysis shows that S. globosus subsp. peregrinus is clustered with its type subspecies (i.e., subsp. globosus), and the significant difference in branch length between them indicates a large variation in their evolutionary rates. These results provide new insights into the Apocynaceae of China.